Education and skills development under the CAREC program a scoping study. (Metro Manila, Philippines Asian Development Bank, 2019)
The global employment and skills landscape is changing fast as fueled by the fourth industrial revolution. Investing in human development is essential to meet the needs of rapidly evolving competitive labor markets and achieve sustainable economic growth. Recognizing this, the CAREC Programs 2030 strategy features human development as one of its five operational priorities and specifies education as a key area of focus. This report identifies important opportunities to harmonize education and skill standards, enhance student and worker mobility, strengthen labor market information and movement, and facilitate knowledge exchange.
Keywords: Educational innovations; Technical education; Electronic books